If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 4) + (x + 2) = 0 Reorder the terms: (4 + x) + (x + 2) = 0 Remove parenthesis around (4 + x) 4 + x + (x + 2) = 0 Reorder the terms: 4 + x + (2 + x) = 0 Remove parenthesis around (2 + x) 4 + x + 2 + x = 0 Reorder the terms: 4 + 2 + x + x = 0 Combine like terms: 4 + 2 = 6 6 + x + x = 0 Combine like terms: x + x = 2x 6 + 2x = 0 Solving 6 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 0 + -6 2x = 0 + -6 Combine like terms: 0 + -6 = -6 2x = -6 Divide each side by '2'. x = -3 Simplifying x = -3
| 0=(5x^4)-(30x^2) | | 5(x+10)=2(2+x) | | 3(3x-7)=2x-56 | | -4v+13v+5=6v+32 | | x/9+2=5 | | 2x(-1-2y)+3y=0 | | 10=2(x+4) | | x/5-6=5 | | 5(7x+5)=55 | | 4y-5=6+3(y-1) | | 2(6x+1)=-82 | | 5,333336+2.34x=3 | | 2(6x+11)=-82 | | 3x(-5-3y)-2y=7 | | -5/6+7/9 | | -23=1-8x | | w/7=9 | | 5=7x-9 | | 2w+3x+13y+4w+8x-4y= | | 6+17w=-15+14w | | -7b-7=42 | | 18-5n=2n+4 | | 4.2x-12.1=-3.7 | | -5/8+4/3 | | 8-9x=-28 | | 2(x+3)x=0 | | 5/8-4/3 | | 7v^3-9v^2= | | -2n-11x+30=0 | | 16+11d=60 | | 7p^2+52p-32= | | 4n-9=3 |